Association of thrombocytopenia with outcome following adult living donor liver transplantation. (29th August 2016) - Pamecha, Viniyendra; Mahansaria, Shyam Sunder; Kumar, Senthil; Bharathy, Kishore Gurumoorthy Subramanya; Sasturkar, Shridhar Vasantrao; Sinha, Piyush Kumar; Kumar, Niteen; Kumar, Vaibhaw
Summary: This study aimed to evaluate the association of postoperative thrombocytopenia with outcome following adult living donor liver transplantation (LDLT) for end‐stage liver disease (ESLD). It was a prospective study of 120 consecutive adult LDLT from September 2012 to May 2015. Preoperative platelet counts (PLTs) and postoperative PLTs were recorded at regular intervals till 3 months after LDLT. Univariate and multivariate analyses were performed. The median pretransplant PLT was 61 × 10 9 /l. The lowest median PLT after LDLT was observed on POD 3. Patients were stratified into low platelet group ( n = 83) with PLT <30 × 10 9 /l and high platelet group ( n = 37) with PLT ≥30 × 10 9 /l. Patients with PLT <30 × 10 9 /l had statistically significant higher grade III/IV complication ( P = 0.001), early graft dysfunction ( P = 0.01), sepsis ( P = 0.001), and prolonged ascites drainage ( P = 0.002). On multivariate analysis, PLT<30 × 10 9 /l was identified as an independent risk factor for grade III/IV complications ( P = 0.005). Overall, patients survival was significantly different between two groups ( P = 0.04), but this predictive value was lost in patients who survived more than 90 days ( P = 0.37). Postoperative PLT of <30 × 10 9 /l was a strong predictor of major postoperative complications and is associated with early graft dysfunction, prolonged ascites drainage, and sepsis. The perioperative mortality rate was high in the thrombocytopenia group.